Um estudo sobre o conceito de densidade do conjunto dos números racionais e do conjunto dos números irracionais: uma abordagem com tecnologias - Santos, Alan Silva dos (2017)
This research aims to analyze, through a didactic sequence, the students' conceptions of an mathematics university course that involve characteristics and properties of rational numbers and irrational numbers, as well as the concept of density of the respective sets in the set of real numbers. The research employs both digital technologies, through GeoGebra software, and non-digital technologies. The studies carried out through a review of the literature and the proposed activities allowed to formulate/refine the problematization around which the investigative procedures developed with a group of undergraduates in Mathematics were developed and which involved questions regarding the conceptions of such subjects about the characteristics and properties relative to rational and irrational numbers, as well as concerning the concept of density of the set of rational numbers and the set of irrational numbers. The research, of a qualitative nature, used data collection instruments designed as digital models, in addition to sequences solved without the use of software, together. The collected data were analyzed using contributions from the Theory of Didactic Situations, as well as theoretical elements related to the use of technologies in Mathematics Education. The analyzes also used references related to numerical representational questions and mathematical knowledge modalities (algorithmic, formal and intuitive). The analyzes carried out suggest that the models and strategies employed were efficient in raising the predominant form of the conceptions of the subjects involved; also indicated that the use of didactic strategies conceived in the research allowed for advances in the re-signification of the mathematical knowledge put into play by the subjects